(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
Interactive language learning methods emphasize active participation, communication, and collaboration, making language acquisition more engaging and effective. These methods include role-playing, group discussions, gamification, and digital tools that facilitate real-life communication. Unlike traditional teaching methods that focus heavily on memorization and passive learning, interactive approaches encourage learners to practice language in meaningful contexts. By creating a learner-centered environment, these techniques enhance comprehension, motivation, and fluency while promoting cultural awareness